(3bjO GdChGHO ef GdahGFO hGdYhGFO hGdRhGFOs - (3YHO Gdedc Hf MSjf Hf YHO Gdedc GdYUGej,J (B1111 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH jJYdb HGdbQGf GdYXje aGFOI hYGjOI hRGFOI JJYdb GdChdi Hg JYdb GdPGJ dG GdYQV SejJg bjO GdGhGHO ef GdahGFO hGdYhGFO hGdRhGFO CeG GdahGFO agi GXgGQ s
(3BNQgG (B:s
(3RhGFO ShQI GdfGS hGSeM hLO HGdQVi dYHO GfJ dg dGShGc QGMe gPG eG YfjJ HLeYg hJCdjag hGdMeO ddg Ydi GdJeGe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B256s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs